Factors generating anxiety when learning EFL speaking skills - Rizaldy Hanifa (Universitas Syiah Kuala, 2018)
The mastery of communication skills is undeniably considered the most important aspect in modern-day EFL contexts. Nevertheless, becoming communicatively competent is particularly difficult for foreign language learners as it is influenced by a number of factors including affective factors. Among the several affective factors which affect foreign language learning especially speaking, anxiety emerges to be the crucial one that has a devastating effect on the oral performances of students. This paper reviews the speaking anxiety phenomenon in the field of foreign language learning. The possible factors that cause speaking anxiety to come into play are described and discussed in accordance with the central themes appearing from an examination of relevant literature. The central themes are (1) cognitive factors covering topics, genre, interlocutors, and processing demands; (2) affective factors dealing with feelings towards the topic and/or the participants, and also self-consciousness; and (3) performance factors concerning mode, degree of collaboration, discourse control, planning and rehearsal time, time pressure and environmental conditions. Understanding the nature of this anxiety and the sources it springs from thoroughly should help both teachers and learners to gain more insights and find ways with which to deal with anxiety in EFL classrooms.